2014
DOI: 10.5694/mja13.10823
|View full text |Cite
|
Sign up to set email alerts
|

Topical timolol for a chronic ulcer — a case with its own control

Abstract: A trial of topical timolol solution in a 92-year-old patient with two chronic leg ulcers resulted in rapid healing of the treated ulcer. While this finding needs to be confirmed, topical timolol is a simple, inexpensive therapy that has the potential to help heal refractory wounds. 1 Tang J, Dosal J, Kirsner R. Topical timolol for a refractory wound. J Am Acad Dermatol 2012; 66 (4 Suppl 1): AB12. 2 Tang JC, Dosal J, Kirsner RS. Topical timolol for a refractory wound. Dermatol Surg 2012; 38: 135-138. 3 Drew P, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Further, our studies have shown that catecholamines increase neutrophil dwell time in the wound, delaying healing in an animal wound model, and treatment with βAA reverses this, restoring healing time to normal [73]. We and others have also documented and reported on cases of venous leg ulcers and other chronic wounds in humans that have improved healing after topical timolol application [38,61,62,67]. These multiple laboratory studies and anectdotal clinical reports indicate that βAAs (timolol) promote wound healing and shorten time to healing; thus, a clinical trial is the next logical step to determine if this approach is truly efficacious in the clinical setting of DFUs.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Further, our studies have shown that catecholamines increase neutrophil dwell time in the wound, delaying healing in an animal wound model, and treatment with βAA reverses this, restoring healing time to normal [73]. We and others have also documented and reported on cases of venous leg ulcers and other chronic wounds in humans that have improved healing after topical timolol application [38,61,62,67]. These multiple laboratory studies and anectdotal clinical reports indicate that βAAs (timolol) promote wound healing and shorten time to healing; thus, a clinical trial is the next logical step to determine if this approach is truly efficacious in the clinical setting of DFUs.…”
Section: Discussionmentioning
confidence: 58%
“…The average exposed ocular surface is about 3 cm 2 [32]. Based on the studies using timolol topically for ulcerative hemangiomas [46-54, 56, 60] and the numerous case studies of topical timolol on chronic wounds [39,40,61,62], the maximum dosage used in this study will be 3 drops/3 cm 2 /day, which is equivalent to 0.75 mg/3cm 2 /day ( Table 3). For study patients, depending on the size of the DFU, see Table 3, either topical timolol or placebo drug (non-biologically active gel) will be administered as one drop daily for < 0.5cm 2 to > 0.5-1.9 cm 2 , two drops daily for wound size > 2-2.9 cm 2 , and three drops daily for anything > 3 cm 2 (maximum dose).…”
Section: Drug Management and Record Keepingmentioning
confidence: 99%
“…Our previous work has also shown that catecholamines cross‐talk with Toll‐like receptors in both human MSC and keratinocytes to contribute to the chronic wound pathology (Dasu et al , ). In addition, we (Lev‐Tov et al , ) and others (Braun et al , ; Manahan et al , ; Tang et al , ) have also reported on the efficacy of timolol in improving healing of recalcitrant venous leg ulcers. Herein, we report success using a combination therapy of topical autologous, AMSC‐enriched high‐density lipoaspirate (HDL) and timolol, a beta‐adrenergic antagonist, to heal a venous ulcer.…”
Section: Introductionmentioning
confidence: 74%
“…These findings prompted the authors to use timolol on a stalling venous leg ulcer that had failed multiple advanced treatments (Lev-Tov et al, 2013). Others (Braun et al, 2013;Manahan et al, 2014;Tang et al, 2012) have also reported cases of venous leg ulcers that have improved once a similar dosage of timolol was topically applied to the wound.…”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66][67] Numerous case studies have also reported success in treating chronic, recalcitrant wounds with non-selective topical b-blockers such as timolol and propranolol. [68][69][70][71][72][73][74] Furthermore, two randomized controlled trials including 79 and 69 burn patients found that oral propranolol administration markedly decreases the time needed to receive skin graft and the area needed to be grafted. 75,76 Pyoderma gangrenosum Pyoderma gangrenosum is a rare, ulcerative inflammatory skin disorder with unknown aetiology.…”
Section: Wound Healingmentioning
confidence: 99%